2020
DOI: 10.7759/cureus.7358
|View full text |Cite
|
Sign up to set email alerts
|

Potentially Preventable Mortality in the Pediatric Intensive Care Unit: Findings from a Retrospective Mortality Analysis

Abstract: The goal of this study was to estimate the proportion and causes of potentially preventable mortality among critically ill children admitted to the pediatric intensive care unit (PICU). Methods The medical records of all patients who died in the PICU (age range: one month to 16 years) between January 2014 and December 2015 were evaluated by two independent reviewers to determine whether there had been any delayed recognition of deteriorating conditions, delayed interventions, unintentional/unanticipated harm, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The mortality rate during the one-year study period was 10.42 %. Studies have reported a wide range of mortality rates in PICUs of Pakistan (11.9 to 35%), 12 which is comparable to India, 13 but very high compared to approximately 3% in the USA. 2 Infants were the largest sub-group (45.68%) in the mortality group.…”
Section: Discussionmentioning
confidence: 93%
“…The mortality rate during the one-year study period was 10.42 %. Studies have reported a wide range of mortality rates in PICUs of Pakistan (11.9 to 35%), 12 which is comparable to India, 13 but very high compared to approximately 3% in the USA. 2 Infants were the largest sub-group (45.68%) in the mortality group.…”
Section: Discussionmentioning
confidence: 93%
“…We collected data through a study questionnaire using inpatient medical records by two independent reviewers with a similar protocol as described in a previously published study from our center [ 13 ]. Data collection included demographic details (age, gender, weight, height) as well as clinical details including diagnostic categories, indications for tracheostomy, the day of admission when tracheostomy was done, Pediatric Risk of Mortality (PRISM III) score, and outcome data (duration of mechanical ventilation, hospital length of stay [LOS], intensive care unit LOS, and complications of tracheostomy) [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…We collected data through a study questionnaire using inpatient medical records by two independent reviewers with a similar protocol as described in a previously published study from our center [13]. The most common indications for elective tracheostomy ( Table 2) were PMV (n=24, 50%) and extubation failure (n=9, 18.7%).…”
Section: Data Collection and Analysismentioning
confidence: 99%
“…3 Furthermore, healthcare providers are scarce and due to continuous brain drain are less well-trained in LMICs. 4,5 Even in one of the better intensive care units like ours, the mortality rates remain very high; with the majority of reasons being preventable such as late presentation, delayed recognition of the deteriorating condition, and delayed intervention. 5 PICUs are scarce resources in Pakistan.…”
Section: Introductionmentioning
confidence: 88%
“…4,5 Even in one of the better intensive care units like ours, the mortality rates remain very high; with the majority of reasons being preventable such as late presentation, delayed recognition of the deteriorating condition, and delayed intervention. 5 PICUs are scarce resources in Pakistan. According to a survey done in 2023, there were only 53 PICUs all over Pakistan with a total 667 beds, equating to 0.7 bed for every 100,000 children.6 Within these units, there are only 20 trained paediatric intensivists.…”
Section: Introductionmentioning
confidence: 88%